Information and Communication Technologies in Tourism 2017 : Proceedings of the International Conference in Rome, Italy, January 24-26, 2017 - Schegg, Roland; Stangl, Brigitte (Springer, 2017)
This book presents state-of-the-art research into the application of information and communication technologies to travel and tourism. The range of topics covered is broad, encompassing digital marketing and social media, mobile computing and web design, semantic technologies and recommender systems, augmented and virtual reality, electronic distribution and online travel reviews, MOOC and eLearning, eGovernment, and the sharing economy. There is a particular focus on the development of digital strategies, the impact of big data, and the digital economy. In addition to the description of research advances and innovative ideas, readers will find a number of informative industrial case studies. The contents of the book are based on the 2017 ENTER eTourism conference, held in Rome. The volume will be of interest to all academics and practitioners who wish to keep abreast of the latest developments in eTourism.